2022
DOI: 10.1007/s11845-022-03050-6
|View full text |Cite
|
Sign up to set email alerts
|

The DA VINCI study: is Ireland achieving ESC/EAS guideline–directed LDL-C goals?

Abstract: Background The EU-wide, cross-sectional observational study of lipid-lowering therapy (LLT) use in secondary and primary care (DA VINCI) assessed the proportion of patients achieving low-density lipoprotein cholesterol (LDL-C) goals recommended by the European Society of Cardiology (ESC)/European Atherosclerosis Society (EAS) guidelines and provided an insight into regional use of LLT in Europe, including Ireland. Aims This analysis focuses on data from pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Both the HEYMANS 7,8 and DA VINCI 4,1014 studies showed a consistent pattern of improved LDL-C goal attainment in patients receiving PCKS9i in combination with statins ± ezetimibe compared with those receiving less intensive treatment regimens. In the present CEE cohort, risk-based LDL-C goal attainment was also higher in patients receiving evolocumab combination therapy (Bulgaria: 55%, Czech Republic: 71%, Slovakia: 51%) compared to those with evolocumab alone (Bulgaria: 19%, Czech Republic: 49%, Slovakia: 34%).…”
Section: Discussionmentioning
confidence: 87%
“…Both the HEYMANS 7,8 and DA VINCI 4,1014 studies showed a consistent pattern of improved LDL-C goal attainment in patients receiving PCKS9i in combination with statins ± ezetimibe compared with those receiving less intensive treatment regimens. In the present CEE cohort, risk-based LDL-C goal attainment was also higher in patients receiving evolocumab combination therapy (Bulgaria: 55%, Czech Republic: 71%, Slovakia: 51%) compared to those with evolocumab alone (Bulgaria: 19%, Czech Republic: 49%, Slovakia: 34%).…”
Section: Discussionmentioning
confidence: 87%
“…The extent of lipid problems in Ireland is significant, and lipid management [4,6] and lipid services are inadequate [15,16]. The significance of untreated lipid disorders on population health cannot be overestimated [17,18], and early interventions could have far-reaching consequences on Irish lives and health care resource utilisation.…”
Section: Discussionmentioning
confidence: 99%
“…They make recommendations according to the type and level of evidence supporting or not the best course of action in various circumstances. Despite an enormous effort to develop guidelines, their translation into clinical practice is often slow or challenging [3][4][5][6]. Many with severe hypercholesterolaemia go undetected or inadequately treated [7].…”
Section: Introductionmentioning
confidence: 99%
“…The use of ezetimibe and PCSK9i in combination with statins was low (9% and 1%, respectively), with a higher proportion of patients receiving these combination therapies achieving 2019 ESC/EAS LDL-C goals (37% with ezetimibe and 57% with PCSK9i) compared with statin monotherapy. The DA VINCI overall study [6] and the other studies in various countries provide a wealth of evidence that patients on LLTs often do not achieve guideline-recommended LDL-C levels, and LLTs are often not intensified as recommended by current guidelines [7][8][9][10][11][12][13][14][15][16][17]. A key part of implementing guideline-directed lipid lowering is testing for lipid levels in appropriate patients.…”
Section: Introductionmentioning
confidence: 99%